Genetic aspects of dental caries - Cogulu, Dilsah; Saglam, Ceren (Frontiers in Dental Medicine, 2022)
Dental caries is one of the most common chronic diseases affecting humans in all age groups. Many factors can affect the processes of demineralization and remineralization including oral flora, dietary and oral hygiene habits, saliva composition, salivary flow rate, pH, buffering capacity, morphological features of the teeth, fluoride exposures, and socioeconomic factors. Host genetics may influence many of these factors leading to inter-individual variation in susceptibility to caries. Several genes likely influence individual susceptibility to caries, and these include genes involved in enamel development, saliva function, and immune response. The present review aims to give an overview of the literature focusing on genetic aspects of dental caries.